Retrospective study of the success of dental implants placed in HIV-positive patients - Nadine Cordero Rubinstein; Zhimon Jacobson; Gail Link McCausland; Serge Dibart (SpringerOpen, 2019)
Abstract Background Data related to HIV-positive patients with dental implants is short-termed and limited. Recent data showed that both HIV and antiretroviral therapy (ART) could lead to low bone mineral density (BMD). The aim of this study was to determine the success rate of dental implants in HIV-positive patients. Materials and methods Dental files of 67 HIV-positive patients were selected and reviewed retrospectively, and 18 subjects agreed to return for examination. All implants were evaluated using periapical radiographs that were calibrated to measure bone loss. Crestal bone loss, mobility, and lack of infection were the parameters used to determine implant success. Results All dental implants evaluated lacked mobility and infection. Bone loss averaged 0.5 mm in 3.6 years. Subjects were consistent with maintenance and oral hygiene. Conclusions Within the limitations of this study, the results suggest that the placement of dental implants on HIV-positive patients is safe and effective.